Patterns of landscape - Eplényi, Anna (4D Journal of Landscape Architecture and Garden Art, 2015)
The article starts with a short landscape-painting introduction, and then it will be followed by a case-study demonstrating the role of landscape patterns of a Transylvanian region
Keywords: landscape; pattern